Intracellular infections enhance interleukin-6 and plasminogen activator inhibitor 1 production by cocultivated human adipocytes and THP-1 monocytes - Bouwman, J J M; Diepersloot, R J A; Visseren, F L J (Clinical and vaccine immunology, 2009)
Obesity is associated with a chronic inflammatory state, and adipocyte dysfunction is thought to play a crucial role in this. Infection of adipose tissue may trigger the production of inflammatory cytokines, leading to increased recruitment of macrophages into adipose tissue, which in turn may exacerbate the inflammatory state in obesity. Low-grade inflammation was mimicked in an in vitro coculture model with human adipocytes and THP-1 monocytes. Adipocytes and monocytes were infected with adenovirus, cytomegalovirus (CMV), or influenza A virus. After 48 h, transinfection was evaluated and interleukin-6 (IL-6), tumor necrosis factor alpha (TNF-alpha), adiponectin, and plasminogen activator inhibitor 1 (PAI-1) were measured. IL-6 production was upregulated in cocultures of uninfected adipocytes and THP-1 macrophages in a THP-1 cell number-dependent fashion. IL-6 production by CMV-infected adipocytes was increased relative to that of uninfected adipocytes (P < 0.01). IL-6 production by CMV-infected cocultures was 16- to 37-fold higher than that of uninfected adipocytes (P < 0.001). IL-6 production in influenza A virus-infected cocultures was increased 12- to 20-fold (P < 0.05). Only CMV infection increased levels of PAI-1 in cocultures (fourfold; P < 0.05). Soluble factors produced by THP-1 macrophages rather than by adipocytes were responsible for the increased production of IL-6 in cocultures. Infection of cocultivated human adipocytes and THP-1 monocytes with CMV or influenza A virus led to increased production of IL-6 and PAI-1. Thus, infection of adipose tissue evokes an inflammatory response, leading to adipose tissue dysfunction and subsequent overproduction of IL-6 and PAI-1. This may further compound the atherogenic effects of obesity.